Inclusive economic growth and fiscal intervention: could it reduce poverty, inequality, and unemployment in East Java? - Purwanti, Dyah (Jurnal Ekonomi & Studi Pembangunan, 2024)
Before the COVID-19 pandemic, East Java Province (then abbreviated to East Java) made remarkable achievements in economic growth accompanied by a continuing downward trend in poverty. Then, after the COVID-19 pandemic broke out in 2020, it had a detrimental impact in terms of health, economics and social aspects. Specifically for East Java, the outbreak caused a severe contraction in the economy and significantly increased the number of local unemployed. However, long before COVID-19, East Java was facing wide inequality. Based on these problems, this study evaluates whether inclusive growth and local government fiscal intervention are solutions. These two factors have been recommended by economist as an effective strategies for reducing the triple problem in East Java. Fiscal intervention is interpreted as expenditure policies in economic, education, and health functions. Using panel data regression during 2015-2021, the study documents that economic growth in East Java still needs to be fully inclusive. This is based on the finding that inclusive economic growth does not simultaneously reduce triple problems (poverty, inequality and unemployment). Inclusive growth reduces poverty in East Java, but it has the opposite effect on unemployment and inequality. On the one hand, positive findings are documented in which fiscal intervention in education spending plays a significant role in reducing poverty. Unfortunately, this study failed to find the determining factors that provide a solution to inequality and unemployment in East Java. These evidences certainly have implications for reviewing the quality of inclusive growth and local government expenditure policies.